2020
DOI: 10.3174/ajnr.a6414
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Aspiration versus Stent Retriever Thrombectomy as the Preferred Strategy for Patients with Acute Terminal Internal Carotid Artery Occlusion: A Propensity Score Matching Analysis

Abstract: BACKGROUND AND PURPOSE: There is no consensus on endovascular treatment for terminal ICA. The purpose of this study was to evaluate the comparative safety and efficacy of preferred aspiration thrombectomy and stent retriever thrombectomy for revascularization in patients with isolated terminal ICA occlusion. MATERIALS AND METHODS: We conducted a retrospective analysis of patients with terminal ICA occlusion treated with aspiration thrombectomy or stent retriever thrombectomy in our center, from September 2013 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 27 publications
0
19
2
Order By: Relevance
“…In 2020, Xing et al directly investigated the two MT techniques efficacy in tICA occlusions. Patients treated with the direct aspiration technique achieved significantly higher successful recanalization rates which may explain the slightly better successful recanalization rate in our study compared to previous studies (83.6% vs. 78%) [19,25].…”
Section: Discussioncontrasting
confidence: 52%
“…In 2020, Xing et al directly investigated the two MT techniques efficacy in tICA occlusions. Patients treated with the direct aspiration technique achieved significantly higher successful recanalization rates which may explain the slightly better successful recanalization rate in our study compared to previous studies (83.6% vs. 78%) [19,25].…”
Section: Discussioncontrasting
confidence: 52%
“…Second, the CA procedure is started by advancing a guide catheter that contains an 8-or 9-Fr balloon guiding catheter (BGC) or 6-Fr neurosheath to the proximity of the occluded target vessel, while meniscus-like appearance provides a larger area for contact with the catheter (24). Choosing CA with proximal blood flow arrest by BGC can reduce the risk of ectopic distal thrombosis and increase the effect of flow reversal during aspiration (25)(26)(27).…”
Section: Discussionmentioning
confidence: 99%
“…From these 351 studies, 30 studies were included in the meta-analysis. [ 2 - 5 , 7 , 9 - 10 , 12 , 14 - 22 , 24 - 28 , 30 , 32 , 33 , 36 - 38 , 40 , 41 ] The references of the included studies were manually searched, and no further articles were included. The flow chart of the study selection process is shown in the PRISMA flow diagram in [ Figure 1 ].…”
Section: Resultsmentioning
confidence: 99%